A novel nanoparticle drug delivery system based on PEGylated hemoglobin for cancer therapy. (1st January 2019) - Zhao, Yongmei; Chen, Gang; Meng, Zhengjie; Gong, Guangming; Zhao, Wei; Wang, Kaikai; Liu, Tianqing
Abstract: Proteins such as albumin, gelatin, casein, transferrin, and collagen are widely used as drug delivery systems. However, only albumin-based paclitaxel (PTX) formulation Abraxane ® (PTX-albumin NPs prepared by nab-technology) has been successfully developed for treating metastatic breast cancer clinically due to abundant materials, simple industrial scale-up process, and well tumor-targeting ability. Hemoglobin (Hb) is another protein used for drug delivery with similar advantages. In this study, we successfully synthesized PEG-Hb nanoparticles loading with PTX based on previously well-established acid-denatured method. PEG-Hb-PTX NPs showed enhanced cellular uptake and great cellular inhibition ability in vitro . Moreover, our animal study showed that PEGylated NPs greatly accumulated in tumor tissues and exhibited excellent anticancer activity in vivo. We found that PEG-Hb-PTX NPs possess a better in vivo antitumor effect than the commercially available Taxol ® formulation. We believe that PEG-Hb has great potential as an efficient drug delivery system for further clinic study.